13 Amending Admission Protocol to Reduce Proton Pump Inhibitor-Induced Hyponatraemia on A Specialist Hip Fracture Unit. (6th February 2020) - Darnell, R; Clements, B; Reeve, E; Singh, N
Abstract: Introduction: Hyponatraemia is a common electrolyte disturbance amongst elderly patients. Defined as a sodium concentration below 135 mmol/L, the BNF cites hyponatraemia as a 'rare' side effect of Omeprazole, a common proton pump inhibitor (PPI). In elderly patients, hyponatraemia can have significant morbidity. On our Hip Fracture Unit (HFU) at St Helier Hospital, all patients are commenced on Omeprazole on admission. We conducted a quality improvement project to reduce the incidence of PPI-induced hyponatraemia by altering standard protocol from Omeprazole to Ranitidine. Methods: Phase 1: Retrospective analysis identifying incidence of PPI-induced hyponatraemia, defined as sodium concentration below 133mmol/L on two consecutive readings and resolving on switching to Ranitidine (Group A: n=86). Phase 2: Identifying incidence of hyponatraemia following administration of Ranitidine from admission (Group B: n=62). Exclusion criteria: Patients already on gastric protection or hyponatraemic on presentation. Chi squared analysis to establish statistical significance for risk of hyponatraemia associated with omeprazole. Results: Total number of patients was 148. Age range 60-101 years (median 82 years). Incidence of PPI-induced hyponatraemia in Group A was 10.5% (9 cases). All resolved on switching to ranitidine. Following change in admission protocol to Ranitidine (Group B), incidence of hyponatraemia was 1.6% (1 case). The chance of developing hyponatraemia with Omeprazole was significantly higher than with ranitidine (P=0.0454). Conclusions: 10.5% of admissions to the HFU experienced PPI-induced hyponatraemia. The European Medicines Agency defines side effects occurring at greater than 10% as very common. Whilst 45% of patients were on medication associated with hyponatraemia on admission, the absence of hyponatraemia at presentation and biochemical response when switching to ranitidine, demonstrates this is a significant side effect of PPIs. Given the increased morbidity associated with hyponatraemia, particularly in frail, elderly patients, amending protocol to ranitidine for gastric protection has the potential to reduce harm and improve patient outcomes.